Author Correction: Immune reconstitution therapies: concepts for durable remission in multiple sclerosis. - Lünemann,JD; Ruck,T; Muraro,PA; Bar-Or,A; Wiendl,H (Nat Rev Neurol, 2020)
An amendment to this paper has been published and can be accessed via a link at the top of the paper.